Z Szekspirem w tle. "Opowieść zimowa" Erica Rohmera - Kowalski, Tomasz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The paper aims at analyzing the relationship between Eric Rohmer’s A Tale of Winter (Conte d’hiver, 1992) and Shakespeare’s late comedy. Although both works are entitled similarly, at first glance they have hardly anything in common, aside from one scene in which the two main characters watch Shakespeare’s play staged in a theatre. The author argues, however, that many references to original comedy, both on the level of plot and structure, can be found in Rohmer’s movie, which can therefore be perceived as a loose adaptation of Shakespeare’s work.